In vitro and in vivo evaluation of antioxidant activity, acute toxicity, and antihyperglycemic effect of individual and binary mixtures of crude methanolic extracts of Cucurbita moschata and Bidens pilosa - Hellen Phiri; Agape Lumai; Kadango Zombe; Evelyn Funjika; Peter Mubanga Cheuka; James Nyirenda (PLoS ONE, 2026)
Background Bidens pilosa (BP) and Cucurbita moschata (CM) are used to treat diabetes traditionally. Little is known scientifically about the toxicity and efficacy of the individual or binary mixtures on blood-sugar-lowering effects. Hence, this study carried out toxicity studies and examined the antidiabetic effects of these plants to support traditional knowledge. We report the phytochemical composition, total phenolic (TPC), flavonoid content (TFC), and antioxidant activity of individual and mixed methanolic BP and CM leaf extracts. We also report acute toxicity of the individual extracts. This study is the first to investigate the antidiabetic effects of a combined BP and CM leaf extract in alloxan-induced diabetic mice. Aim The study aimed to determine toxicity and the blood-glucose-lowering effects of individual and combined mixtures of BP and CM on alloxan-induced diabetic mice. Materials and Methods Acute toxicity of the extracts was assessed through the LD 50 assay in rats after oral administration. TFC was measured using a modified aluminium chloride colourimetric method, while TPC was measured using the Folin-Ciocalteau’s method. The antioxidant activity was analysed using the Ferric Reducing Antioxidant Power (FRAP) method, 2,2-diphenyl-1-picrylhydrazyl (DPPH), and hydrogen peroxide radical scavenging assay. We investigated the antihyperglycemic effect of the extracts by measuring their blood-glucose-lowering effect in alloxan-induced diabetic mice. Results No mortality or significant behavioural changes were observed at doses up to 10,000 mg/kg, suggesting a high safety margin for the two plants under study. Oral administration of the combined leaf extract of BP and CM in the ratios of 1:1, 1:2, and 2:1 w/w % showed that the BP: CM (1:2) extract at the concentration of 500 mg/kg significantly reduced blood glucose levels from 17.2 ± 0.15 mmol/L to 3.9 ± 0.04 mmol/L. The positive control, glibenclamide (5 mg/kg), reduced blood glucose levels from 17.0 mmol/L to 4.1 mmol/L, respectively (p < 0.0001). Conclusion In vivo results of this study suggest that a combined leaf extract of B. pilosa and C. moschata may provide glucose-lowering effects as seen in mice though this is yet to be tested in humans. In addition, the extract may provide a nutritional source among Zambians. Acute toxicity results suggest that C. moschata and B. pilosa extracts are essentially safe, supporting their use as food and a potential source of nutraceuticals.